PERANCANGAN SISTEM INFORMASI PENDAFTARAN MURID BARU PADA PAUD KANGGURU KECIL BERBASIS WEB - Hanif Rabbani Zubair (2022)
The development of the digital era in the use of technology in community activities, especially in the field of education. Technology that now makes daily activities easier can help school management, especially registration. Done manually using paper media. This can cause several obstacles, namely when data is needed and the time it takes to fill out forms and the dissemination of registration information is limited to using only brochures/pamphlets. This study aims to create a web-based information system to help reduce obstacles that may arise in the previous system. Registration information system, starting from providing registration information, filling out registration forms, uploading requirements, checking data, and reporting registration results. The design of this information system uses the Waterfall approach. The programming languages used are HTML, CSS, and PHP which are supported by MySQL as the database. The results of the registration information system on the Little Kangaroo PAUD website can facilitate the registration process and the dissemination of information online.